(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The exchange rate in Iraq is witnessing a lengthy discussion to bridge the gap between the official and parallel rates, but this gap occurs as a result of market behavior in the Iraqi economy, as monetary policy in Iraq, especially after the second amendment to the official exchange rate (1320), works to reduce the gap that occurs due to small... Merchants who carry out parallel sterilization within the market itself. Parallel sterilization means parallel sterilization, which is non-centralized or parallel behavior within the money market and is linked to the demand for cash for liquidity purposes in light of the availability of the opportunity cost of anticipating what can be called the basic or large expected interest return in holding cash. The research problem was represented by a statement. The phenomenon of parallel sterilization in the market in light of the measures taken by monetary policy? As for the goal of the research, it focused on a group of goals, but the most prominent goals are reducing the gap between the two prices in light of the rise in oil revenues and the increase in foreign reserves at the Central Bank of Iraq. The research hypothesis was that there is a significant effect between demand on the exchange rate and supply. As for the most important conclusion that the research came out of Parallel sterilization is a phenomenon generated as a result of parallel demand, which constitutes a heavy burden on monetary policy tools. The most important recommendation is the necessity of reducing the gap between the two prices in light of monetary policy measures.